2015
DOI: 10.1080/00036846.2015.1073843
|View full text |Cite
|
Sign up to set email alerts
|

Economic costs and impacts of climate-induced sea-level rise and storm surge in Canadian coastal provinces: a CGE approach

Abstract: We estimated the economic costs and impacts of future sea-level rise (SLR) and storm surge due to climate change in Canada's coastal provinces using regional, dynamic computable general equilibrium models that track provincial welfare, GDP, trade, prices and inputs over the 2009-2054 period. We also assessed the economic costs of coastal adaptation investments, to determine whether such investments can be justified on economic grounds. Results indicated that SLR and storm surge could cost Canada in the range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Further adaptation examples can be found in urban areas near the Fraser River floodplain, an area that is highly vulnerable to sea level rise due to low-lying geology and dense population (Yumagulova and Vertinsky 2017). A recent analysis found that the costs of sea level related damage to on-shore built infrastructure would be higher in coastal BC than any other coastal region in Canada (Withey et al 2016). Regional models of sea level rise and seasonal climatic variability patterns would improve the ability of coastal managers to predict flood hazards and associated risk factors for the region.…”
Section: Communities and Marine Infrastructurementioning
confidence: 99%
“…Further adaptation examples can be found in urban areas near the Fraser River floodplain, an area that is highly vulnerable to sea level rise due to low-lying geology and dense population (Yumagulova and Vertinsky 2017). A recent analysis found that the costs of sea level related damage to on-shore built infrastructure would be higher in coastal BC than any other coastal region in Canada (Withey et al 2016). Regional models of sea level rise and seasonal climatic variability patterns would improve the ability of coastal managers to predict flood hazards and associated risk factors for the region.…”
Section: Communities and Marine Infrastructurementioning
confidence: 99%
“…A recent analysis found that the costs of sea level related damage to on-shore built infrastructure would be higher in coastal BC than any other coastal region in Canada [108].…”
Section: Sea Level Risementioning
confidence: 99%
“…The examined investments and funding for adaptation include agricultural sector investments (Arndt et al, 2015(Arndt et al, , 2011Bosello et al, 2018;Calzadilla et al, 2013Calzadilla et al, , 2014Elshennawy et al, 2016;Robinson et al, 2012;Zidouemba, 2017), funding of adaptation in developing regions (Ouraich and Tyner, 2018;Schenker and Stephan, 2014), coastal protection investments (Elshennawy et al, 2016;Parrado et al, 2020;Withey et al, 2016), decrease in investments in risky areas (Husby et al, 2016), utilization of insurance and catastrophic bonds (Thirawat et al, 2017), public investments in adaptation (Bachner et al, 2019;Hirte et al, 2018;Hoffmann, 2019;Hoffmann and Stephan, 2018) and adaptation measure of an artificial beach enhancement (Nakajima et al, 2020).…”
Section: How Adaptation Is Addressed In the Computable General Equili...mentioning
confidence: 99%